Inventory of Large Mammals in Ujung Kulon National Park, Banten Province - Zulia Pratiwi; Diva Novi Sandrian; Ayu Octavia; Nisa Luthfiah; Riska Rahmawati; Silvia Riskina Said; Neneng Nuraliah (Jurnal Natur Indonesia, 2023)
The National Park has a diverse ecosystem for the preservation of flora and fauna, making Ujung Kulon National Park a habitat for endemic and protected fauna. Large mammals are one of the many animals found in TNUK, especially those with protected status. This study aims to determine the diversity of large mammal species in Ujung Kulon National Park. The research was conducted on September 27–29, 2022, in Ujung Kulon National Park, which is located at the western tip of Java Island, precisely in Sumur and Cimanggu Districts, Pandeglang Regency, Banten Province. The method used was the cruising method using exploratory descriptive data analysis. The results showed that there were two types of large mammals, namely ungulate mammals and primate mammals. The number obtained was 10 types of mammal species belonging to 7 different families. Large mammals found include Rhinoceros sondaicus, Muntiacus muntjak, Cervus timorensis, Hylobates moloch, Presbytis comata, Trachypitecus auratus, Macaca fascicularis, Sus scrofa, Tragulus javanicus, and Bubalus bubalis. Most of the large mammals found are endemic mammals with protected status. Of the large mammals found, the most common were hoofed mammals. With this study, the public has an awareness of the importance of maintaining the diversity of fauna and flora in Ujung Kulon National Park.